1993
DOI: 10.1039/an9931801167
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of ethanol in all types of alcoholic beverages by near-infrared derivative spectrometry

Abstract: A rapid and accurate method has been developed for the direct determination of ethanol in all types of alcoholic beverages. The method, which does not require any sample treatment (except for simple de-gassing for beer samples or dilution with distilled water for spirits), is based on the use of the first derivative of the near-infrared absorbance spectrum. Measurements, carried out between the 1680 nm peak and the 1703 nm valley, provide a typical calibration graph [dA/dh = 0.00002 + 0.01 27c (where c is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…The sensor signals may for example be based on some other major components (implicitly present in the data) which themselves correlate with the concentrations of the Y-reference chemicals. It is well documented, however, that NIR spectra contain information on for instance the ethanol content [24,25], giving some credence to a direct interpretation. More work on these aspects will also be presented elsewhere.…”
Section: Calibrations For Chemical Componentsmetabolites and Substratesmentioning
confidence: 98%
“…The sensor signals may for example be based on some other major components (implicitly present in the data) which themselves correlate with the concentrations of the Y-reference chemicals. It is well documented, however, that NIR spectra contain information on for instance the ethanol content [24,25], giving some credence to a direct interpretation. More work on these aspects will also be presented elsewhere.…”
Section: Calibrations For Chemical Componentsmetabolites and Substratesmentioning
confidence: 98%
“…Therefore, was suggested in this system design to process and differentiate that voltage reading which was assigned to different ethanol concentration. The proposed alcohol detector system used the method of direct determination of ethanol by near-infrared (NIR) derivative spectrometry to determine the concentration of ethanol in any liquid samples up to 25 % v/v with a regression coefficient of 0.999992 [7]. The regression coefficient value was approximated to be one as the graph is almost linear.…”
Section: System Designmentioning
confidence: 99%
“…The main characteristic in developing this alcohol photonics detector is the determination of optimum optical wavelength. However, referring [7], it was found that the light source must be operated at a wavelength of 1680 nm where the ethanol absorbance is dominant at that particular wavelength. From the research, it was found that the Indium gallium arsenide (InGaAs) infrared LED L10823-01 series manufactured by Hamamatsu operates at wavelength range from 1600 nm to 1700 nm.…”
Section: Introductionmentioning
confidence: 98%
“…We can find also selective enzymatic methods (Beutler, 1988) and many instrumental determinations performed by gas chromatography (Wang, Choong, Su, & Lee, 2003), high-performance liquid chromatography (Yarita et al, 2002), amperometry (Paixão, Corbo, & Bertotti, 2002;Pisoschi, Pop, Serban, & Negulescu, 2012), infrared spectrometry (Gallignani, Garrigues, & de la Guardia, 1993;Lachenmeier, 2007), FIA-spectrophotometry (Pinyou, Youngvises, & Jakmunee, 2011) and even Raman spectroscopy (Boyaci, Genis, Guven, Tamer, & Alper, 2012), among others. Some of these methods have been published recently, which indicates that determination of ethanol in alcoholic beverages continues being a target for research.…”
Section: Introductionmentioning
confidence: 99%